Çiçek Derman Bibliography - Mehlika Karagözoğlu (Türk Kütüphaneciliği)
Çiçek Derman is a prominent artist who wrote many books both as an academician and an illuminator. This study introduces the Çiçek Derman Bibliography published by Medine Akgül in 2010. The book consists of introduction, biography and six chapters. These chapters are “Prof. Dr. Fatma Çiçek Derman Bibliography” which includes books, articles, radio and television broadcasts, essays about her, essays ready to publish and conference declarations, “Academic Consultancies”, “Membership in Selection Committee of Turkish Islamic Arts and Science Committees”, “Arbitration and Editorial Boards She Joined”, “Exhibitions” and “Compilation of Her Works”.